Copies of Lulac Mailgrams - PAUL JOHNSON (Tufts Archival Research Center, 2007)
Illegible/Difficult to Read; Memo from Paul Johnson to Fred Panzer regarding copies of League of United Latin American Citizens mailgrams to members of the House Ways and Means Committee. Includes mailgrams themselves, which congratulate members on opposing cigarette excise tax. Argues excise taxes disadvantage the hispanic community by adversely affecting low income people, by closing small businesses, and by encouraging an underground market.